Kebijakan Perubahan Lahan dalam Pembangunan Food Estate di Kalimantan Tengah - Puspita Ayu, Katriani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2022)
Permen LHK No. 24/2020 is a land use policy for Indonesia’s food security through food estates program. The program aims to increase the added value of local agricultural production in order to increase employment, low food prices, and the development of large-scale agricultural businesses. According to regulation issud by LHK, food estate policy has the potential to change forest areas into agricultural land because it is legalized by the government through Undang-Undang Cipta Kerja. The consequences of implementing this policy are including environmental damage, increased conflict and poor land use management which is not in accordance with the Central Kalimantan spatial plan (RTRWP). The food estate program becomes government's priority in achieving food security through the State supports in a fast and less bureaucracy process on land licensing. This indicates that the process of land clearing for food estate violates forestry and land use regulations.